About the rhythmicity of the prose paraphrase of Mikołaj Rej’s David’s Psalter - Kowalska, Danuta (Philology as the Ordering of Chaos: Language and Text Studies. Ad honorem Professoris Marci Cybulski, 2018)
The article deals with the notion of rhythmicity in the prose paraphrase of Mikołaj Rej’s David’s Psalter. The analysis of chosen syntactic (anaphora, alliteration, etymological figures) and phonetic rhetorical terms makes it possible to show the translator’s meticulous work on his selection of lexemes and their distribution in a single sentence or a verse. Rej did not follow the ciceronianism of the Renaissance and instead he made references to the rhetoric tradition of the Middle Ages, especially the artistic ars dictandi, which makes his prose style so characteristic. Rej modelled himself in this respect on Campensis, the opponent of the classical rhetorics. Present in the Polish translation, the terms are subordinate to the sound structure of the text and they make it closer not only to the traditional style of the Psalter’s translations, but they also imitate, to some extent, the outer characteristics of the Hebrew psalmic poetry, its melody, rhythmicity and orality.